Trajectory Generation Module Design for Robot Manipulators - Souza, Gabriel; Dutra, Gustavo; Zanlucchi, Jose Jean-Paul (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
Following the technology demands created by Industry 4.0, robot manipulator popularity has increased significantly. One of the crucial aspects on its application is the calculation of a suitable and eﬃcient trajectory to the objective states, converting action plans into control references for the robot system controller. This paper presents the development of a generic trajectory planner, were simple and generic techniques are favored for maintenance and portability, thus it was created as an independent module to be included as part of a modular generic architecture that wields those advantages. It’s composed of two nested processes, the first responsible for generating a point-by-point trajectory and the following, an internal process responsible for calculating a satisfactory set of controller references to achieve the generated trajectory point, using a numerical optimization approach. The explored optimization technique is based on using the robots Direct Geometric Model (DGM) and the Jacobian pseudo-inverse, to iterate searching for local minima in the error surface, using the pseudo-inverse to direct the actuator references towards a solution. A didactic example is presented to clarify on the required information and steps, and to observe parameter eﬀects on behavior and results. A discussion of restrictions and optimized solutions is also carried along the text.